2021
DOI: 10.3390/ijms22157912
|View full text |Cite
|
Sign up to set email alerts
|

Seeing Keratinocyte Proteins through the Looking Glass of Intrinsic Disorder

Abstract: Epidermal keratinocyte proteins include many with an eccentric amino acid content (compositional bias), atypical ultrastructural fate (built-in protease sensitivity), or assembly visible at the light microscope level (cytoplasmic granules). However, when considered through the looking glass of intrinsic disorder (ID), these apparent oddities seem quite expected. Keratinocyte proteins with highly repetitive motifs are of low complexity but high adaptation, providing polymers (e.g., profilaggrin) for proteolysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 108 publications
0
11
0
Order By: Relevance
“…Proline disrupts or terminates secondary structures in proteins, and glutamine and lysine are the targets of transglutamination, a process critical for epidermal cornification 4 . In addition, all three amino acids are associated with a high propensity to form disordered protein segments 30 , suggesting that SEDC proteins and the carboxy-terminal domain of SFTPs of caecilians are intrinsically disordered proteins, thus resembling their counterparts in mammals 31 33 . Sequence alignment showed similarities between SEDC proteins of caecilians and small proline-rich proteins (SPRRs) of mammals (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Proline disrupts or terminates secondary structures in proteins, and glutamine and lysine are the targets of transglutamination, a process critical for epidermal cornification 4 . In addition, all three amino acids are associated with a high propensity to form disordered protein segments 30 , suggesting that SEDC proteins and the carboxy-terminal domain of SFTPs of caecilians are intrinsically disordered proteins, thus resembling their counterparts in mammals 31 33 . Sequence alignment showed similarities between SEDC proteins of caecilians and small proline-rich proteins (SPRRs) of mammals (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently published data demonstrated that treatment of full-thickness skin model with cytokine mixture leads to a decrease in the thickness of the nucleated epidermis (Todorović et al 2022 ). In a long-term skin model with nanometer-thick fibronectin–gelatin-coated normal human dermal fibroblasts, a 5-day incubation with rhIL-17A causes a decrease in the thickness of the stratum granulosum (Singh et al 2020 ). Moreover, higher concentrations of cytokine mixture result in tissue disruption and detachment of the stratum corneum (Todorović et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, this skin model mimics the route of exposure for dermally applied chemicals and therefore allows for testing conditions closer to the intended situation of use. Moreover, inflammatory stimuli could drive the development of the psoriasis-like phenotype in this model (Singh et al 2020 ). Psoriasis is a chronic inflammatory disease characterized by prominent epidermal proliferation and keratinocyte hyperplasia with altered differentiation and scale production.…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis is supported by a new model incorporating a recently published flDPnn algorithm [37] which predicts protein and/or nucleic acid interactions with disordered regions of the ICD of BP180 (Figure 3c). It seems that the under-investigated field of intrinsic disorder in keratinocyte proteomes is gathering pace [38]. The implications of these intrinsic structural features of BP180 to its function as a component of HD and other structures are discussed in Section 4, Section 6, and Section 7 below.…”
Section: Structure Of Bp180mentioning
confidence: 99%